2011
DOI: 10.1111/j.1365-2486.2011.02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in N2O flux dynamics in a Danish wetland – effects of plant‐mediated gas transport of N2O and O2 following changes in water level and soil mineral‐N availability

Abstract: Temporal trends of N 2 O fluxes across the soil-atmosphere interface were determined using continuous flux chamber measurements over an entire growing season of a subsurface aerating macrophyte (Phalaris arundinacea) in a nonmanaged Danish wetland. Observed N 2 O fluxes were linked to changes in subsurface N 2 O and O 2 concentrations, water level (WL), light intensity as well as mineral-N availability. Weekly concentration profiles showed that seasonal variations in N 2 O concentrations were directly linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 33 publications
3
59
2
2
Order By: Relevance
“…N 2 O emissions vary considerably and have been influenced by several key factors, such as soil WFPS, pH, C supply, and the weather conditions (Lin et al 2009;Jørgensen et al 2012). However, in this study we only observed significant relation between N 2 O emissions and the 5 cm soil temperatures in 2005.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…N 2 O emissions vary considerably and have been influenced by several key factors, such as soil WFPS, pH, C supply, and the weather conditions (Lin et al 2009;Jørgensen et al 2012). However, in this study we only observed significant relation between N 2 O emissions and the 5 cm soil temperatures in 2005.…”
Section: Discussioncontrasting
confidence: 52%
“…Moreover, temporal dynamics of soil water regime in wetland soils is sensitive to seasonal and inter-annual weather patterns, which will affect the environmental drivers for N-transformation processes (Jørgensen et al 2012). On the plateau, the precipitation trend since 1960 has shown an overall slight increase with highly seasonal and inter-annual variations Kang et al 2010) and this trend will continue in the future (Piao et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, the transport of oxygen to anaerobic zones stimulates heterotrophic degradation of organic matter, but at the same time stimulates oxidation of CH 4 (Kao-Kniffin et al, 2010) and suppress CH 4 production due to increase in redox potential (Laanbroek, 2010;SuttonGrier and Megonigal, 2011). RCG may further increase the emissions of reduced soil gases as the aerenchyma tissues act as a conduit for the direct transport of, for example, CH 4 and N 2 O produced in soil (Joabsson et al, 1999;Jørgensen et al, 2012). Also, RCG can decrease N 2 O emissions by assimilation of mineral N, which reduces the availability of electron acceptors (nitrate) for denitrifying microorganisms (Roobroeck et al, 2010).…”
Section: Introductionmentioning
confidence: 99%